The study of a novel high selectivity pyrenyl-based fluorescence probe with aggregation-induced emission characteristics for Fe3+ detection designed by a structure modulation strategy. Issue 48 (2nd December 2022) - Liu, Sen; Li, Jun; Hou, Tianjiao; Shen, Xuan
Abstract : The past decades have witnessed the feat of fluorescent probes for Fe 3+ detection, where eliminating the interference by other metal ions plays a pivotal role in its detection by probes in complex environments. Abstract : The past decades have witnessed the feat of fluorescent probes for Fe 3+ detection, where eliminating the interference by other metal ions plays a pivotal role in its detection by probes in complex environments. Herein, by taking advantage of the substituent effects, the electron-withdrawing group (EWG) –CF3 and electron-donating group (EDG) –CH3 were introduced to 2-(1-pyrenyl)pyridine (pypyr) to prepare two turn-off fluorescence probes, 5-trifluoromethyl-2-(1-pyrenyl)pyridine (pypyr-CF3 ) and 5-methyl-2-(1-pyrenyl)pyridine (pypyr-CH3 ). Intriguingly, both probes displayed novel aggregation-induced emission (AIE) characteristics in MeCN/H2 O mixtures and the size and morphology of the aggregated particles were studied via DLS and TEM. By the modulation strategy, pypyr-CF3 can detect Fe 3+ in the presence of 29 different metal ions without interference. Comparatively, pypyr-CH3 experienced serious interference from other metal ions such as Hg 2+ and Zr 4+ . Besides, pypyr-CF3 not only demonstrated a higher photoluminescence quantum yield (PLQY) of 65.25% and wider pH adaptability but is also capable of Fe 3+ detection over a wide pH range of 2–11 with a short response time (5 seconds). A plausible quenching mechanism based on the inner filter effect has also been demonstrated. More importantly, the versatile applications of pypyr-CF3, such as the quantitative analysis of Fe 3+ in actual water samples, anti-forgery ink, fingerprint identification, etc., further corroborate its superb capabilities. This study aims to lend concrete support to the design and selectivity modulation of probes.